A novel Patient-Specific Three-Dimensional Printing Template Based on External Fixation for Pelvic Screw Insertion. Issue 2 (1st February 2022) - Zhou, Kaihua; Tao, Xingguang; Pan, Fugen; Luo, Congfeng; Yang, Huilin
Abstract: Purpose: To investigate the clinical effect of novel patient-specific 3D printing templates based on external fixation for pelvic screw insertion compared with the fluoro-navigation technique. Materials and methods: We retrospectively studied 18 pelvic fracture patients from July 2017 to July 2018. For analysis, patients were divided into two groups: the template group (15 screws in 8 patients) and the fluoro-navigation group (22 screws in 10 patients). The screw insertion time, radiation exposure time, and accuracy of the screw insertion as evaluated by postoperative CT scans were analyzed. Results: In the template group, the average screw insertion time (11.5 ± 2.3 min/screw) was significantly 50.6% less than that in the fluoro-navigation group (23.3 ± 3.1 min/screw; P < 0.05). The average time of X-ray exposure in the template group (11.5 ± 3.9 s/screw) was also significantly 39.8% less than in the fluoro-navigation group (19.1 ± 2.5 s/screw; P < 0.05). In the template group, the mean deviation distance and angle between the actual and planned screw position was 2.6 ± 0.2 mm and 2 ± 0.3°. Conclusions: The patient-specific template based on external fixation can guide the insertion of the pelvic screw accurately and safely while significantly reducing operation and radiation exposure time.